2021
DOI: 10.3390/jcm10061168
|View full text |Cite
|
Sign up to set email alerts
|

Elderly Patients in a Large Nephrology Unit: Who Are Our Old, Old-Old and Oldest-Old Patients?

Abstract: The world population is aging, and the prevalence of chronic kidney disease (CKD) is increasing. Whether this increase is also due to the methods currently being used to assess kidney function in the elderly is still a matter of discussion. We aimed to describe the actual referral pattern of CKD patients in a large nephrology unit and test whether the use of different formulae to estimate kidney function could affect the staging and the need for specialist care in the older subset of our population. In 2019, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…In a cohort of 1992 nephrology patients, Torreggiani et al found that the highest heterogeneity was observed with BIS-1. [60] We could not confirm that observation since, according to our results, MDRD and BIS-1 showed the most similar estimation curve when compared with CKD-EPI (Figures S1-S4). Different clinical settings and the distribution of elderly patients may explain the difference.…”
Section: Concordance Between Ckd-epi and Different Egfr Equationsmentioning
confidence: 57%
See 1 more Smart Citation
“…In a cohort of 1992 nephrology patients, Torreggiani et al found that the highest heterogeneity was observed with BIS-1. [60] We could not confirm that observation since, according to our results, MDRD and BIS-1 showed the most similar estimation curve when compared with CKD-EPI (Figures S1-S4). Different clinical settings and the distribution of elderly patients may explain the difference.…”
Section: Concordance Between Ckd-epi and Different Egfr Equationsmentioning
confidence: 57%
“…In a cohort of 1992 patients, Torreggiani et al [60] found that estimated glomerular filtration rate (eGFR) decreased with age regardless of which equation was used. Analyzing the correlations between CKD-EPI and other eGFR equations, the highest heterogeneity was observed with BIS-1; the revised Lund-Malmo tended to underestimate eGFR while MDRD overestimated it.…”
Section: Egfr Estimates and Patient's Agementioning
confidence: 99%
“…Which is the best method to estimate the eGFR in older patients is still debated. In a recent paper, Torregiani and co-authors (31) found that the most frequently used formulae based on the creatinine values had similar performances in classifying the stage of CKD independently of patients' age. In the general CKD population (32), the formulae that contain both creatinine and cystatin C values are more precise and accurate to estimate GFR with respect to those that are based solely on creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…Diese Herausforderung in medizinischer und psychologischer Sicht trifft alle Altersstufen der Patient:innen mit chronischen Nierenerkrankungen: sowohl Kinder und Jugendliche als auch Erwachsene bin ins Seniorenalter. In den Industrienationen sind die Senioren die am raschesten wachsende Gruppe von Patient:innen mit chronischer Nierenerkrankung, die aktuell mindestens 20 % der Dialysepopulation darstellt [ 1 , 2 ].…”
Section: Einführungunclassified